2013
DOI: 10.1111/ijn.12094
|View full text |Cite
|
Sign up to set email alerts
|

Traditional practices used by the infertile women to become pregnant and their effects on the quality of life

Abstract: The present research was planned to determine the traditional practices used by infertile women to become pregnant and their effects on the quality of life. A hospital-based, descriptive and cross-sectional study. Participant Information Forms and SF-36 quality of life scales were applied to 269 women diagnosed as infertile. Some of the infertile women (32.7%) were determined to use a traditional method. The traditional methods used by women included herbal remedies (those edible and drinkable) (87.5%), sittin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The prevalence of TCT use varies by country. It was reported that TCT use prevalence was 49.6% in Iran, 44.7% in Jordan, 41.0% in Lebanon, 39.8% in Israel, 36.5% in Sierra-Leone, 30.6% in Denmark, and 29.5% in the USA (Ayaz and Yaman Efe, 2008;Boivin and Schmidt, 2009;Edirne, Arica, Gucuk, Yildizhan, Kolusari, Adali ve Can 2010;Günay, Cetinkaya, Nacar and Aydin, 2005;Kırca and Sis Çelik, 2016;Timur Taşhan and Aksoy Derya, 2013). In Turkey, the prevalence ranged from 9.3%-82.0% in the east, 27.3%-61.5% in the Central Anatolia and 51.0%-65.0% in the west (Dehghan, Mokhtarabadi and Heidari, 2018;Engin and Pasinlioğlu, 2002;Ghazeeri, Awwad, Alameddine, Younes and Naja 2012;James, Taidy-Leigh, Bah, Kanu, Kangbai and Sevalie, 2018;Özkan, Karaca and Sarak, 2018;Porat-Katz, Eldar-Geva, Kahane, Laufer, Younis, Radin and Paltiel, 2015;Smith, et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of TCT use varies by country. It was reported that TCT use prevalence was 49.6% in Iran, 44.7% in Jordan, 41.0% in Lebanon, 39.8% in Israel, 36.5% in Sierra-Leone, 30.6% in Denmark, and 29.5% in the USA (Ayaz and Yaman Efe, 2008;Boivin and Schmidt, 2009;Edirne, Arica, Gucuk, Yildizhan, Kolusari, Adali ve Can 2010;Günay, Cetinkaya, Nacar and Aydin, 2005;Kırca and Sis Çelik, 2016;Timur Taşhan and Aksoy Derya, 2013). In Turkey, the prevalence ranged from 9.3%-82.0% in the east, 27.3%-61.5% in the Central Anatolia and 51.0%-65.0% in the west (Dehghan, Mokhtarabadi and Heidari, 2018;Engin and Pasinlioğlu, 2002;Ghazeeri, Awwad, Alameddine, Younes and Naja 2012;James, Taidy-Leigh, Bah, Kanu, Kangbai and Sevalie, 2018;Özkan, Karaca and Sarak, 2018;Porat-Katz, Eldar-Geva, Kahane, Laufer, Younis, Radin and Paltiel, 2015;Smith, et al, 2010).…”
Section: Discussionmentioning
confidence: 99%